Migratory Dates, Breeding Phenology, and Reproductive Success of European Turtle Doves between Lowlands and Highest Breeding Habitats in North Africa - Mansouri, Ismail; Mounir, Mohamed; Squalli, Wafae; Elhanafi, Laila; Dakki, Mohamed; El Ghadraoui, Lahsen (International Journal of Zoology, 2020)
The migratory time, breeding chronology, and reproductive success of the European turtle doves (Streptopelia turtur) were studied in Midelt as a high-altitude breeding habitat and Beni Mellal as a low-altitude breeding site from 2015 to 2018 in Morocco. Migration dates, breeding phenology, and breeding success were recorded from March to October for each season. As a result, during four years, arrival dates were earlier at the low breeding site, while departure dates were earlier at the high breeding site. Similarly, breeding phenology from nest building to fledging was early at low-altitude site. On the other hand, with four breeding seasons and 893 nests (467 at Midelt and 426 at Beni Mellal), average breeding success was 57% of chicks at Midelt compared to 60.15% at Beni Mellal. Moreover, at Midelt, 18.89% of eggs and 10.54% of chicks were predated, while at Beni Mellal 21.80% of eggs and 4.65% of chicks were deserted due to human disturbance. As a response, at Midelt breeding period was shorter and shifted to hot periods to ensure better reproductive success. Finally, our results highlight that the turtle dove breeding season is later and shorter at breeding highlands, which might allow this bird to avoid the vigorous climate conditions at mountains and their effect on reproductive success.